Disability does not negatively impact linguistic visual-spatial processing for hearing adult learners of a signed language - Joyce, Taylor Renee; Quinto-Pozos, David; Singleton, Jenny L.; DiLeo, Michael (Frontiers in Communication, 2023)
The majority of adult American Sign Language (ASL) learners are hearing and previously naïve to signed language. Thus, they must simultaneously acquire a new modality as well as a specific language. Researchers have studied both first and second signed language learners to probe modality-unique drivers of acquisition. In the former group, atypically developing signers have provided an especially unique axis—namely, disability— for analyzing the intersection of language, modality, and cognition. Here, we provide an analysis of disability in adult, hearing second language (L2) learners of ASL, with respect to both linguistic and non-linguistic visual processing. College-level ASL students completed an ASL phonological-discrimination task as well as non-linguistic and linguistic (ASL) versions of a perspective-taking task. Accuracy and response time measures for the tests were compared between a neurodiverse group with reported diagnoses (e.g. ADHD, learning disability) and a neurotypical group with no reported diagnoses. The neurodiverse group collectively had lower accuracy compared to the neurotypical group only on the non-linguistic perspective-taking task. Moreover, the group who specifically identified as having a learning disability performed worse than the other diagnostic groups. We interpret these findings as demonstrating, crucially, that the signed modality itself does not disadvantage neurodiverse learners, even with demonstrated deficits compared to peers in visuospatial processing. We do recommend that signed language instructors specifically support and monitor students in this diagnostic category to ensure development of visual-spatial skills and processing in signed language, given general performance on the administered tasks compared to the neurotypical and diagnostic groups.